No effects of the theta-frequency transcranial electrical stimulation for recall, attention control, and relation integration in working memory - Ociepka, Michał; Chinta, Suvarna Rekha; Basoń, Paweł; Chuderski, Adam (Frontiers in Human Neuroscience, 2024)
Recent studies have suggested that transcranial alternating current stimulation (tACS), and especially the theta-frequency tACS, can improve human performance on working memory tasks. However, evidence to date is mixed. Moreover, the two WM tasks applied most frequently, namely the n-back and change-detection tasks, might not constitute canonical measures of WM capacity. In a relatively large sample of young healthy participants (N = 62), we administered a more canonical WM task that required stimuli recall, as well as we applied two WM tasks tapping into other key WM functions: attention control (the antisaccade task) and relational integration (the graph mapping task). The participants performed these three tasks three times: during the left frontal 5.5-Hz and the left parietal 5.5-Hz tACS session as well as during the sham session, with a random order of sessions.Attentional vigilance and subjective experience were monitored. We observed no significant WM task accuracy gains for neither tACS session, as compared to sham. The results suggest that canonical measures of WM capacity are strongly stable in time and hardly affected by theta-frequency tACS.